Analyzing Five Types of Deixis in Cruella Movie: Pragmatics Analysis - Akita Putri Artelu; Dewi Rosaria Indah (Journal of English Language Teaching and Literature, 2023)
In the pragmatics analysis, there are various kinds, one of which is deixis. It takes five forms according to Levinson (1983) that are person deixis (the first person, the second person, and the third person), place deixis, time deixis, discourse deixis, and social deixis. The research was created to analyze the five degenerative forms found in Cruella movie. This research uses descriptive method. The data is drawn from the sentences of the characters in the Cruella movie and analyzed using the theory of Levinson (1983). The results of this research are that deixis consists of five forms, namely: [1] person deixis, consisting of the first people (I, my), the second person (you), and the third person (they), [2] place deixis, which are London and outside, [3] time deixis, which are afternoon, now, and 5:00 a.m., [4] discourse deixis, which are it and that, and [5] social deixis, which is madam.